The Effects Of Eurycoma Longifolia Extract And Eurycomanone On The Steroidogenesis In Mouse Leydig Cells - Ahmed, Nor Amira Khurshid (2018)
Eurycoma longifolia Jack (Tongkat Ali) is one of the most popular traditional plants found in the tropical rainforest of Southeast Asia, especially in Malaysia and Indonesia. Although E. longifolia is widely used as traditional medicine, little is understood of the in vitro effect on Leydig cells; the testosterone-producing cells. Therefore, the effect of a standardised E. longifolia extract (F2) and pure compound, eurycomanone (EN) on the productions of testosterone, estrogen and aromatase in mouse Leydig cells were determined in this study, whereby the Formestane (FM) was used as a positive control. The effect of F2, EN and FM on the cell viability was first determined using MTT assay.